HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PERGELANGAN TANGAN DENGAN HASIL KETEPATAN SMASH BOLA VOLI PADA CLUB 3GN PEKANBARU - Indah Septiani S Depari; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problems faced at the Pekanbaru 3GN club were several unexpected phenomena, namely the results of the smash were still not optimal, this was due to the athlete's physique that was not optimal such as leg muscle power and wrist flexibility which were not optimal, so the results of the smash carried out by the athlete were not optimal. powerful and easy to catch. The purpose of this study is to study the relationship between leg muscle power, wrist flexibility and leg muscle power relations and hand movements together with the results of the 3GN Pekanbaru smash club. This research was conducted at the 3GN Pekanbaru club field, Jl. February 2023. The population in this study were 14 Pekanbaru 3GN athletes. This research was conducted using correlation research, a study designed to determine the level of relationship between different variables in the population. The data obtained were analyzed by simple product moment correlation. Based on the analysis obtained a correlation coefficient of rcount (0.724) > rtable (0.553), thus Ha is accepted. This means that there is a relationship between leg muscle power and wrist flexibility with the results of smash accuracy, where the provisions for the correlation of a variable with other variables are determined from rcount> rtable and significant (Sugiono, 2008: 258).Keywords: Leg muscle power, wrist flexibility, smash results